ANALISIS DAMPAK LALU LINTAS AKIBAT BEROPERASINYA HOTEL IBIS DAN APARTEMEN CANDI LAND TERHADAP RUAS JALAN DIPONEGORO KOTA SEMARANG - Fariz Arinal Noor Ananta; Rahmat Navis Hasanta; Wahyudi Kusharjoko; Amelia Kusuma Indriastuti (Jurnal Karya Teknik Sipil, 2014)
Ibis Hotel and Candi Land Apartment located at Diponegoro street currently are built into the new residential alternative in Semarang. This will trigger trip generation in the future, thus will increase congestion in the area. Therefore, it is important to assess the impact of the hotel and apartement operations. This study aims to predict the trip generation, evaluate the performance of the existing road network, predict the performance of the network after the operation of Ibis Hotel and Candi Land Apartment and propose the solutions to encounter the conditions. Analyses of the performance of segments, signalized intersection and roundabout refer to IHCM 1997. Trip generation prediction of hotel and apartment refer to Department of Transportation regulation. Based on the analysis, Ibis Hotel and Candi Land Apartment trip generation amounted to 341 pcu/hour. The existing degree of saturation (DS) of the nearest road segments are 1.40 on Sriwijaya street, 1.64 on Diponegoro street, 1.00 on Veteran street, 0.57 on Pahlawan street, 0.85 on Kawi street, 0.84 on Sultan Agung street, and 1.55 on S. Parman street. The degree of saturation of Pahlawan intersection is 1.92 (North). Thus, the degree of saturation of Diponegoro Park roundabout is 1,00 (CD inweave Diponegoro street – Kawi street). After the operation of Ibis Hotel and Candi Land Apartment, the degree of saturation of Pahlawan intersection will increase up to 6,97%. The Degree os saturation of Diponegoro Park roundabout will also increase for about 5,12%. The proposed solution on Pahlawan intersection are to make Veteran street a one way road leaving the intersection and reset the green time. This treatment will decrease the degree of saturation up to 21 – 32 %. The proposed solution on the nearest road segments are to widen the road segments that cause a decrease on the degree of saturation for about 17-31%. Whilst, the proposed solution for Diponegoro Roundabout is to give road signs which are expected to reduce conflict on the weaving area.